Optimization of surface roughness in milling of EN 24 steel with WC-Coated inserts using response surface methodology: analysis using surface integrity microstructural characterizations - Patil, Shashwath; Sathish, Thanikodi; Rao, P. S.; Prabhudev, M. S.; Vijayan, V.; Rajkumar, S.; Sharma, Shubham; Kumar, Abhinav; Abbas, Mohamed; Makki, Emad (Frontiers in Materials, 2024)
EN 24 steel is a nickel-chromium-molybdenum composition of medium-carbon and high-strength steel alloys. It is ideal for producing components for heavy-duty projects as it can retain significant effect values at low temperatures. The present work aims at optimizing process parameters to achieve minimum surface integrity during the milling of EN 24 steel with coated tungsten carbide tool inserts (WC). Four process factors, viz., feed rate, cutting speed, depth of cut, and cutting fluid, were selected for experimental work, with four levels for each parameter. The design of experiments (DOE) based on the Central Composite Design of Response Surface Methodology has been employed in this study. Analysis of variance (ANOVA) was employed for optimization and mathematical models to obtain output parameters. The response optimum combination for tungsten carbide inserts was identified as cutting speed (CS) at 149.507 m/min, feed rate (FR) at 340.27 mm/min, depth of cut (DOC) at 0.599 mm, and cutting fluid (CF) at 12.50 l/min for achieving minimum surface irregularities of 0.301 µm, were achieved during multi-objective optimization. Scanning electron microscope (SEM), analysis exhibits the morphologies of the machined workpiece surface at CS 130 m/min, FR 325 mm/min, DOC 0.50 mm, and CF 22.5 l/min, along with the SEM microstructure of the machined workpiece at CS 120 m/min, FR 350 mm/min, DOC 0.45 mm, and CF 15 l/min. Profilometry is utilized to find the machined workpiece's morphology and surface irregularities.